ChemInform Abstract: Biological Sulfate Reduction for Treatment of Gypsum Contaminated Soils, Sediments, and Solid Wastes. Issue 22 (15th May 2015) - Kijjanapanich, Pimluck; Annachhatre, Ajit P.; Lens, Piet N. L.
Abstract: Review: 131 refs.